Women's Empowerment Strategy in Building MSMEs in Tanjungpinang City, Riau Islands - Nika Purnamasari; Joana Evelin; Ahmad Riyadi; Agustika Safitri; Nikodemus Niko (Formosa Journal of Applied Sciences, 2023)
The Micro, Small Medium Enterprise (MSMEs) sector involving women in Tanjungpinang City includes culinary businesses, services, and agribusiness. The objective of these women-involved MSMEs is to promote gender equality, enhance social well-being, create employment opportunities, and provide financial services to the wider community, particularly women. The research employed a qualitative methodology, gathering data from fieldwork and literature studies, including sources such as books, online news, and scholarly journals. Based on this study, identified empowerment strategies include education and skill training, access to financial resources, and social network support. Recommendations include the need for a sustainable women's empowerment program planning framework, implying the necessity for policies that support more effective women's empowerment efforts.